Dynamic Analyses of Transcriptome and Metabolic Profiling: Revealing Molecular Insight of Aroma Synthesis of Mango (Mangifera indica L. Var. Tainong) - Xin, Ming; Li, Changbao; Khoo, Hock Eng; Li, Li; He, Xuemei; Yi, Ping; Tang, Yayuan; Sun, Jian (Frontiers in Plant Science, 2021)
This study aimed to evaluate the changes in aromatic components and other chemical properties of Tainong mango during fruit development, ripening, and storage. As the volatiles of Tainong mango and their related molecular mechanisms remain unclear, volatile profile, metabonomics, and transcriptome analyses were applied to investigate the molecular determinants of the synthesis of aroma components in mango during fruit development and storage. Total acids, total sugar, total carotenoids, enzyme activities of the mango pulp samples were also determined. Volatile components of the mango pulp samples were identified using a gas chromatography-mass spectrometric method. Ribonucleic acid (RNA) sequences of the samples were analyzed by real-time polymerase chain reaction. The results showed that 181 volatiles were isolated and identified in the fruit at seven stages. Compared to the other stages, mango collected on day 8 and day 12 had higher concentrations of 17 volatile components, especially (E,Z)-2,6-nonadienal, 53384 transcripts were also detected through RNA-Seq. The differentially expressed genes analyses included catalytic activity, transferase activity, adenosine diphosphate binding, transcription factor activity, and oxidoreductase activity. α-Pinene content and expression of the differentially expressed genes involved in terpenoid metabolism and enzyme activities in the terpenoid metabolic pathways gradually increased during the maturity of the fruit, and had maximum values at day 8 of storage. Moreover, the integrative analyses revealed potential molecular insights of mango development and aroma formation in the fruit.